Termites community as environmental bioindicators in highlands: a case study in eastern slopes of Mount Slamet, Central Java - TEGUH PRIBADI; RIKA RAFFIUDIN; IDHAM SAKTI HARAHAP (Society for Indonesian Biodiversity, 2011)
Pribadi T, Raffiudin R, Harahap IS (2011) Termites community as environmental bioindicators in highlands: a case study in eastern slopes of Mount Slamet, Central Java. Biodiversitas 12: 235-240. Termites ecological behavior is much affected by land use change and disturbance level. Their variation in diversity can be used as bioindicator of environmental quality. However, termite community response to land use changes and habitat disturbance in highland ecosystems remains poorly understood. This study was conducted to investigate the response of termite community to land use intensification and to explore their role as environmental bioindicator in Mount Slamet. A standard survey protocol was used to collect termites in five land use types of various disturbance levels, i.e. protected forest, recreation forest, production forest, agroforestry, and urban area. It was found two termite families i.e. Rhinotermitidae andTermitidae with seven species, i.e. Schedorhinotermes javanicus, Procapritermes sp, Pericapritermes semarangi, Macrotermes gilvus, Microtermes insperatus, Nasutitermes javanicus, and N. matangensis. Termite species’ richness and evenness, Shannon-Wiener index, relative abundance, and biomass of termite were declined along with the land use types and disturbance level from protected forest to urban area. Habitat disturbance was the main declining factor of termite diversity. Termite composition changed along with the land usedisturbance level. Soil feeding termites were sensitive to the disturbance – they were not found in urban area. Hence, their presence or absence can be used as environmental bioindicator to detect habitat disturbance.